Chair's Welcome (EAAE Annual Conference Proceedings, 2023)
The NEB is the seed of a project full of hope that has started in Europe, but its momentum is unstoppable and wants to spread to the rest of the world. Within Spain, our school of architecture is currently a reference institution in this field. The ETSAM cooperates with the Spanish Government, Directorate-General for Urban Agenda and Architecture, to analyze, promote and position our country’s contribution to the NEB at an international level.